RELATION TIMELINESS COMPLEMENTARY FEEDING WITH NUTRITIONAL STATUS OF INFANTS AGED 6-12 MONTH - Retnosari Widowati; Atika; Dominicus Husada (UNIVERSITAS AIRLANGGA, 2022)
Background: Infants aged six months and over have increased nutritional needs so that breast milk is no longer fulfilled because it is necessary to provide complementary foods for breast milk (MP-ASI) to reduce and prevent malnutrition. The provision of MP-ASI has a relationship with nutritional status. This study aims to know about the relationship between timeliness of complementary foods with the nutritional status of infants aged 6-12 months in the working area of ​​the Margorejo Health Center. Methods: The research design used an observational cross sectional. The population in this study were all mothers who had babies aged 6-12 months in the working area of ​​the Margorejo Health Center. Sampling technique using total sampling and the sample size was 64 respondents. Data were collected using a questionnaire. The research variables were timeliness, frequency, quantity, diversity of species and suitability of MP-ASI texture. Data analysis using contingency coefficient test to determine the correlation between the independent variable and the dependent variable. Results: Timeliness of complementary foods was shown by 53,13% respondents while 46,87% of them not on time in timeliness of complementary foods. The results showed that no relationship between the timeliness of complementary feeding with nutritional status with p value=0,64. Conclusion: This study shows that there is no relationship between the timeliness of complementary feeding with the nutritional status of infants. Keywords: complementary feeding, timeliness, frequency, quantity, types of diversity, texture suitability, nutritional status